Proposed indicators for selecting needy participants for the Vulnerable Women's Benefit (VWB) Program in urban Bangladesh - Ahmed, Akhter; Bakhtiar, M. Mehrab; Quabili, Wahid; Parvin, Aklima; Ghostlaw, Julie (International Food Policy Research Institute, 2022)
Bangladesh has extensive experience with targeted social safety net programs. Most of these programs are widely credited with providing the poor access to food and improving their livelihoods. However, the need for assistance is overwhelming. According to the latest poverty estimates, 24.3 percent of the country’s 163 million people were poor in 2016 (BBS 2019). Improving program targeting to reach the poorest of the poor effectively is needed to address the wide gap between the resources available for safety net programs and those in need of support. Targeting effectiveness indicates the extent to which program benefits are received by the neediest versus the less needy or non-needy population. A well-targeted intervention improves the real income, food consumption, and nutrition of the neediest without providing those benefits to members of society who are better off. As such, targeting benefits to those most in need is a cost-effective way of implementing a program. Upon request from the Ministry of Women and Children Affairs (MoWCA) and the World Food Programme (WFP) in Bangladesh, the International Food Policy Research Institute (IFPRI) undertook this study to develop indicators for targeting the urban poor through the Vulnerable Women’s Benefit (VWB) program in Bangladesh.